Thematic Structure in Chinese and Spanish: A Contrastive Analysis to Be Applied in Foreign Language Teaching and Translation - Rovira-Esteva, Sara; Liu, Shiyang (Íkala, Revista de Lenguaje y Cultura, 2016)
Although the concept of theme or topic has been widely researched both in Chinese and Spanish, no studies have been carried out about their thematic structure from the perspective of contrastive linguistics. Taking Loar’s theory (2011) as a starting point, we have carried out a contrastive analysis and the results show that Chinese has not only a higher tendency to use topicalised constructions than Spanish, but also a wider range of constructions of this type. Both languages can use topicalisers and have also in common the word classes that can occupy the topic position. Nevertheless, Spanish is more flexible regarding the position of the topic. All these aspects are illustrated with numerous examples offering possible equivalents between this language pair. Therefore, this study can help to fill in a gap in both the field of Chinese as a foreign language and didactics of translation.